Virtual reality training for radiation safety in cardiac catheterization laboratories - an integrated study - Fujiwara, Asahi; Fujimoto, Sota; Ishikawa, Ren; Tanaka, Aoi (Radiation protection dosimetry, 2024)
The advent of fluoroscopically guided cardiology procedures has greatly improved patient outcomes but has also increased occupational radiation exposure for healthcare professionals, leading to adverse health effects such as radiation-induced cataracts, alopecia, and cancer. This emphasizes the need for effective radiation safety training. Traditional training methods, often based on passive learning, fail to simulate the dynamic catheterization laboratory environment adequately. Virtual Reality (VR) offers a promising alternative by providing immersive, interactive experiences that mimic real-world scenarios without the risks of actual radiation exposure. Our study aims to assess the effectiveness of VR-based radiation safety training compared to traditional methods. We conducted a prospective cohort study involving 48 healthcare professionals in a catheterization lab setting. Participants underwent a 1-hour self-directed VR training session using Virtual Medical Coaching’s RadSafe VR software, which simulates real-world clinical scenarios. Pre- and post-intervention radiation dose levels were measured using personal dosimeters at the eye, chest, and pelvis. Knowledge and skills were assessed through tests, and feedback was gathered through surveys and interviews. Statistical analysis revealed significant reductions in radiation exposure across all professional groups after VR training. For cardiologists, the eye dose dropped by 21.88% (from 2.88 mSv to 2.25 mSv), the chest dose decreased by 21.65% (from 4.11 mSv to 3.22 mSv), and the pelvis dose went down by 21.84% (from 2.06 mSv to 1.61 mSv). Perioperative nurses experienced similar reductions, with eye doses decreasing by 14.74% (from 1.56 mSv to 1.33 mSv), chest doses by 26.92% (from 2.6 mSv to 1.9 mSv), and pelvis doses by 26.92% (from 1.3 mSv to 0.95 mSv). Radiographers saw their eye doses reduced by 18.95% (from 0.95 mSv to 0.77 mSv), chest doses by 42.11% (from 1.9 mSv to 1.1 mSv), and pelvis doses by 27.63% (from 0.76 mSv to 0.55 mSv).Participants reported enhanced engagement, improved understanding of radiation safety, and a preference for VR over traditional methods. A cost analysis also demonstrated the economic advantages of VR training, with significant savings in staff time and rental costs compared to traditional methods. Our findings suggest that VR is a highly effective and cost-efficient training tool for radiation safety in healthcare, offering significant benefits over traditional training approaches.